2003
DOI: 10.1097/01.mp.0000056985.01062.e7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Utility of Ductal Lavage and Ductoscopy in Breast Cancer—A Retrospective Analysis of Mastectomy Specimens

Abstract: Early detection of breast lesions continues to be an important goal in the management of breast cancer. At present, mammographic imaging in addition to physical examination is the main screening method for the detection of cancer. Fiberoptic ductoscopy and duct lavage are being recently used to evaluate patients at risk for breast cancer. Both techniques examine the nipple and central duct area to identify intraductal lesions. In this study, we examined the frequency of involvement of these structures in maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…While only discharged ducts are cannulated by ductoscopy, radiological modalities can detect even intraductal lesions without discharge in asymptomatic patients. 2 studies that examined mastectomy specimens reported that 14-30% of intraductal carcinomas did not have the in situ component [14,73]. These observations raise the possibility that a significant percentage of patients undergoing surgery would not have an intraductal component and therefore MD would not be able to directly visualize some intraductal lesions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While only discharged ducts are cannulated by ductoscopy, radiological modalities can detect even intraductal lesions without discharge in asymptomatic patients. 2 studies that examined mastectomy specimens reported that 14-30% of intraductal carcinomas did not have the in situ component [14,73]. These observations raise the possibility that a significant percentage of patients undergoing surgery would not have an intraductal component and therefore MD would not be able to directly visualize some intraductal lesions.…”
Section: Discussionmentioning
confidence: 67%
“…Researchers were able to depict the lactiferous ducts up to 2-3.3 cm on average, whereby the greatest peripheral depth was 7.5-10 cm [6,8,11,12]. On the other hand, some authors insist on the use of ductoscopy solely for central ducts [13,14]. …”
Section: Ductoscopic Technique and Indicationsmentioning
confidence: 99%
“…Badve et al published a study that indicated a significant number of cancers do not involve central areas or do not contain a significant intraductal component. 18 Additionally, in most cases only 1 or 2 fluid-yielding ducts per breast can be successfully cannulated from approximately 6-8 ducts present in the nipple of a normal breast. 4,5 For ducts known to harbor cancers, some are not sampled by lavage.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported low sensitivity of DL in detecting breast carcinoma in patients undergoing mastectomy for carcinoma [85,86]. A plausible explanation is that DL only samples cells from intraductal processes; about 15 to 30% of invasive cancers lack an intraductal components [87,88]. For DL specimens with atypia below the level of malignancy, the clinical significance of such findings is not known.…”
Section: Ductal Lavagementioning
confidence: 81%